AI-Driven Automation in Software Testing: Enabling SME Adoption - Sothy Sundara, Raju; Wai Yie, Leong (INTI International University, 2025)
The rapid evolution of the software industry has positioned Artificial Intelligence (AI) as a game-changer in software testing, enabling Quality Assurance (QA) teams to deliver higher-quality software with greater speed and efficiency. Despite these advantages, many small and medium-sized enterprises (SMEs) are hesitant to adopt AI into their software testing due to financial limitations, time constraints, and lack of technical skill resources. The study aims to address these challenges by proposing a framework that enables SMEs to implement AI-based automation in software testing aligned with their operational requirements. The research methodology combines a planned survey and a literature review to identify the commonly used automation tools and assess their impact on product quality. The ultimate goal is to develop a cost-effective, practical process innovation framework tailored to support Malaysian SMEs in adopting AI for software testing.